DIALEKTIKA PERBEDAAN INTERPRETASI UMBRELLA CLAUSE DALAM BILLATERAL INVESTMENT TREATIES SEBAGAI PERLINDUNGAN INVESTOR DALAM PUTUSAN ARBITRASE ICSID SGS V. PAKISTAN DAN SGS V. PHILIPPINE - Fitri, Alfa (UNES Law Review, 2023)
Investor-state dispute settlement in current developments has become a problem that often arises in international investment affairs. There are two different objectives, where investors aim to get the maximum profitability and host states aim to benefit from investment while taking into account the national interest in the country. However, the difference in objectives still has something in common, namely investors and host states have equal treatment of their respective rights protected by Bilateral Investment Treaties (BIT) or Contractual Commitments which ultimately conflict gives birth to disputes. The umbrela clause is present in the BIT between the parties as an effort to provide protection for related investments from forms of breach of contract that occur. However, problems arise when two ICSID rulings are born from which give different interpretations of the umbrella clause. This paper is doctrinal with secondary qualitative data collection. The problem approach used in this study is a conceptual approach, by examining the umbrella clause both from previous arbitration awards and expert opinions.This study resulted in conclusions that emphasized the breakfast theory of jurisprudence as the main factor that determines judges in making different interpretations of umbrella clause